GAMBARAN LINGKUNGAN KERJA, KARAKTERISTIK INDIVIDU DAN STRES KERJA PERAWAT RUMAH SAKIT UMUM AVISENA DI CIMAHI - Yuliadi, Hendri; Sumiyati, Sumiyati; Purnama, Ridwan (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose - The purpose of this study is to see the description of work environment, individual characteristics and job stressDesign/methodology/approachh - The design of this study was cross sectional method. This research uses descriptive approach with explanatory survey method. The nurses analysis unit is 73 people. Data collection using questionnaire. The analysis technique used is descriptive technique by using frequency distributionFindings - Based on the results of the research using descriptive analysis, the results obtained that work environment in the quite conducive category, individual characteristics in the good category, and job stress in the quite high category. Originality/value -Â The differences in this study located on an object research , time research , a measuring instrument , literature that used , the theory that is used and the results of the study.